Impact of caffeine dose on bone healing with tricalcium silicate in a rat tibial defect model - Kaya, Berk; Ocak, Mevlut Sinan; Dundar, Serkan; Ozercan, Ibrahim Hanifi (Elsevier, 2026)
Objective: This study aimed to evaluate the effects of different doses of systemically administered caffeine on bone healing and to assess whether a tricalcium silicate-based biomaterial can mitigate its adverse effects in a rat tibial defect model. Study Design: Seventy-two male Sprague Dawley rats (8 weeks old) were randomly assigned to six groups (n=12). Bilateral tibial defects were created under general anesthesia. In three groups, the defects were filled with Neo-Putty; in the other three, defects were left empty. Caffeine was administered daily via oral gavage at 3 mg/100 g or 10 mg/100 g for 30 days. Histological analysis was performed to assess osteoblast activity, bone formation, inflammation, and fibrosis. Statistical comparisons were conducted among groups. Results: The highest osteoblast activity and new bone formation were observed in the control group, while the lowest values occurred in the high-dose caffeine + NeoPutty group. Inflammation and fibrotic tissue formation increased in the caffeine-treated groups, particularly with high-dose caffeine. NeoPutty improved bone healing outcomes but could not completely prevent the deleterious effects of high-dose caffeine. Conclusions: High-dose caffeine impairs bone healing by increasing inflammation and reducing osteoblast activity. NeoPutty shows partial protective effects, but its regenerative performance is compromised under systemic metabolic stress. These findings emphasize the need to consider patient-specific systemic factors when using bioceramic materials for bone regeneration.
Keywords: Animal model; Histopathology; Caffeine; Bone formation